Hubungan Antara Self Image Dengan Hedonisme Pada Siswa SMA Islam Terpadu Ukhuwah Banjarmasin - Fitri Zehra (Universitas Merdeka Madiun, 2024)
Fitri, Relationship between Self Image and Hedonism in Ukhuwah Banjarmasin Integrated Islamic High School Students, Ushuluddin and Humanities Faculty, Antasari Banjarmasin State Islamic University, Jalan Pendarapan Guntung Manggis Village, Banjarbaru City, South Kalimantan. The current generation is very vulnerable to modernization, so it is affected by today's modernity. Most of today's youth are affected by globalization which has negative consequences. This is caused by the feelings of teenagers, especially teenagers who are still unstable because of their identity crisis. This is a difficult period of psychological development in adolescents. Due to the increasing complexity of modern life, people are increasingly choosing patterns of behavior that differentiate them from one another in terms of their lifestyle choices. The hedonistic lifestyle view that material pleasure is the main goal of life. Adolescents who tend towards hedonism often try to harmonize their lifestyle with their peer group which is reflected in certain symbols, such as product brands as markers of their hedonistic values. This phenomenon represents the adjustment process that many teenagers go through to achieve social acceptance. The research method used in this research is quantitative. Based on the r count (Pearson Correlations) it is known that the r count for the relationship between Self Image (X) and Hedonism (Y) is 0.060 <r table 0.349, it can be concluded that there is a negative relationship between the Self Image variable and the Hedonism variable.